Fast Switching of Bright Whiteness in Channeled Hydrogel Networks - Eklund, Amanda (Adv Funct Mater, 2020)
Beside pigment absorption and reflection by periodic photonic structures, natural species often use light scattering to achieve whiteness. Synthetic hydrogels offer opportunities in stimuli‐responsive materials and devices; however, they are not conventionally considered as ideal materials to achieve high whiteness by scattering due to the ill‐defined porosities and the low refractive index contrast between the polymer and water. Herein, a poly(N‐isopropylacrylamide) hydrogel network with percolated empty channels (ch‐PNIPAm) is demonstrated to possess switchable bright whiteness upon temperature changes, obtained by removing the physical agarose gel in a semi‐interpenetrating network of agarose and PNIPAm. The hydrogel is highly transparent at room temperature and becomes brightly white above 35 °C. Compared to conventional PNIPAm, the ch‐PNIPAm hydrogel exhibits 80% higher reflectance at 800 nm and 18 times faster phase transition kinetics. The nanoscopic channels in the ch‐PNIPAm facilitate water diffusion upon phase transition, thus enabling the formation of smaller pores and enhanced whiteness in the gel. Furthermore, fast photothermally triggered response down to tens of milliseconds can be achieved. This unique property of the ch‐PNIPAm hydrogel to efficiently scatter visible light can be potentially used for, e.g., smart windows, optical switches, and, as demonstrated in this report, thermoresponsive color displays.